Making space: Spirituality and mental health - Leibrich, Julie (Mental health, religion & culture, 2002)
This paper was the Mary Hemingway Rees Memorial Lecture, delivered at the XXIst World Assembly for Mental Health, Vancouver, Canada, 2001. The author had recently completed a period of appointment as the New Zealand Commissioner for Mental Health. In this lecture, the author puts in a moving plea - as a survivior of mental illness - for considering both spirituality and mental health in terms of the experience of the self. She talks about the value of communication particularly by sharing experiences via personal stories. The author goes on to contrast communication and control, and to emphasize the importance of making space in order to accept our own and others' imperfections and vulnerabilities. Attention is drawn to the work of Baruk (1978, 1998, 1999, 2000). She also discusses the way in which mental illness can lead to spiritual progress, and ultimately to mental health. The original version of the talk contained further pictorial illustrations; for technical reasons it would be difficult to reproduce all of them here in the journal. Most of the illustrative material consisted of photographs by the author, including the two photographs that are reproduced in this paper.